Exploring students’ perception on the use of Instagram as a platform in Creative Writing course - Tria Mellinia Satya Pratiwi; Noor Eka Chandra; Elvina Arapah (Journal of English Language Teaching and Learning (JETLE), 2023)
As a product of Information and Communication Technology (ICT), the commonly-used social media Instagram offers a new platform of digital writing with unique features that could facilitate and accommodate the exploration of creative writing genre. Through this study, 27 university students’ perception were explored with qualitative descriptive study using open-ended questionnaire, interview and documentation to find out how they perceived this new platform in their writing journey in comparison to university website or traditional means like printed paper. For the findings, variety of students perception were showed in three different spectrums using thematic analysis: 1) majority of the students perceived their experience as positive one due to Instagram benefits as source of inspiration, creativity endeavour and larger engagement for their writing product; 2) some of the students also offered their negative experience in regards to word limitation and insecurity of uploading to public; 3) meanwhile, the more neutral one admitted that Instagram’s benefit was just similar to other platforms. This study’s significant can help future lecturer/teacher in adapting and evaluating the advantage and disadvantage of this application implementation for the improvement of future class.